WASTE TO ENERGY: A SUSTAINABLE APPROACH TO WASTE MANAGEMENT AND RENEWABLE ENERGY GENERATION - Aditya Kumar; Vishwajeet Kumar; Dr.Mani Bhushan (International Educational Journal of Science and Engineering, 2025)
The increasing global waste generation poses significant environmental and economic challenges. WTE allows waste to be converted into energy which reduces the need for landfills. Here, the key features of various WTE technologies including incineration, gasification, pyrolysis and anaerobic digestion are described considering the criteria of efficiency, the environment and economics. Explain and discuss the benefits and risks of adopting WTE for reducing greenhouse gases, strengthening energy security and recovering raw resources and look also at the possible issues such as high capital requirements, negative public views and challenging regulations. Also, global cases show how WTE has been successfully applied and improved. The last section of the paper talks about WTE in the context of circular economy and sustainable energy policy and gives a summary of future developments.